Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.2307/2963476
|View full text |Cite
|
Sign up to set email alerts
|

Host‐Plant Specialization in Western Palearctic Anthidine Bees (Hymenoptera: Apoidea: Megachilidae)

Abstract: To determine the extent of host—plant specialization, the pollen sources of the 72 anthidiine species (family Megachilidae, subfamily Megachilinae, tribe Anthidiini) of Europe, North Africa, and Asia Minor were investigated by microscopic analysis of ≈ 1800 pollen loads of females. By this measure, 31 species (43%) were oligolectic (relatively specialized to pollen source) at the level of plant tribe, plant subfamily, or plant family. Exclusive pollen sources of these bees throughout their geographic ranges a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
144
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(164 citation statements)
references
References 27 publications
10
144
1
7
Order By: Relevance
“…Most cases of host-plant variation involve shifts in the host-plant visited with little change in diet breadth. This pattern is consistent with previous studies on the evolution of host-plant associations in bees (Müller, 1996a;Sipes and Tepedino, 2005;Patiny et al, 2007;Larkin et al, 2008).…”
Section: Degree Of Host-plant Specializationsupporting
confidence: 93%
See 3 more Smart Citations
“…Most cases of host-plant variation involve shifts in the host-plant visited with little change in diet breadth. This pattern is consistent with previous studies on the evolution of host-plant associations in bees (Müller, 1996a;Sipes and Tepedino, 2005;Patiny et al, 2007;Larkin et al, 2008).…”
Section: Degree Of Host-plant Specializationsupporting
confidence: 93%
“…However, several studies showed that field records are not always reliable enough to confidently determine the host-plant range because field records rarely distinguish between pollen and nectar foraging (e.g. Westrich and Schmidt, 1986;Westrich, 1990;Müller, 1996a;Sipes and Tepedino, 2005;Timmermann and Kuhlmann, unpubl. data.).…”
Section: Host-plant Datamentioning
confidence: 99%
See 2 more Smart Citations
“…According to the current theoretical framework, such generalist species are important to maintain the cohesion and stability of plant-bee networks (Memmott et al 2004). On the other hand, relationships between plants and bees may exhibit phylogenetic components that drive the preferences of a group of bees to a given group of plants (Müller 1996;Patiny et al 2008). Thus, certain bee taxa preferentially visit certain plant families or genera.…”
Section: Introductionmentioning
confidence: 99%